The Effect of Foot Deformity and First Metatarsophalangeal Joint Plantar Pain on Performance in DanceSport Athletes - Zijian Liu; Hiroki Yabiku; Takumi Okunuki; Shuo Chen; Takuma Hoshiba; Toshihiro Maemichi; Hideaki Nagamoto; Yanshu Li; Tsukasa Kumai (MDPI AG, 2022)
Background: Adolescent DanceSport athletes who regularly dance in high heels have a higher possibility of developing hallux valgus deformity and foot pain. We believe that the occurrence of foot disorders may change the loading on their feet, which thus affects the athletic performance of those adolescents. Methods: A total of 63 adolescent DanceSport athletes (16 boys, 47 girls) were included. The plantar pain in the first metatarsophalangeal (1st MTP) joint was evaluated using a questionnaire, and the hallux valgus angle was evaluated using digital photographs (HVAp). The loading values of the plantar pressure while performing relève on demi-pointe were measured using sensor sheets. The participating boys and girls were analyzed separately. Results: The results showed that female adolescent DanceSport athletes with the 1st MTP joint plantar pain showed a decrease in the loading distribution and plantar pressure percentage on the hallux and an increased loading distribution and pressure distribution of the metatarsal head as the HVAp increased. Conclusion: Among adolescent DanceSport athletes with plantar pain in the 1st MTP joint and a large HVAp, the loading manner of the foot may have changed, which may be associated with a decrease in the toe function and performance.